Effect of the menstrual cycle when estimating 1 repetition maximum from the load-velocity relationship during the bench press exercise - García-Pinillos, F.; Lago-Fuentes, C.; Bujalance-Moreno, P.; Pérez-Castilla, A. (The Journal of Strength and Conditioning Research, 2022)
This study aimed to examine the effect of the ovulatory menstrual cycle (MC) when estimating the 1 repetition maximum (1RM) from the individual load-velocity relationship during the bench press (BP) exercise. Nine resistance-trained eumenorrheic women (age: 28.7 ± 3.6 years) were tested in 3 different phases across the MC: menstrual or early follicular phase (i.e., testing between days 1-3), follicular or late follicular phase (i.e., testing between days 7-10), and luteal or mid-luteal phase (i.e., testing between days 19-21). Each testing trial consisted of an incremental loading protocol against 4 loading conditions (˜50-70-80-90% 1RM) in the concentric-only BP exercise. A smartphone application (MyLift) was used to collect the mean velocity (MV) of all repetitions. The 1RM was estimated from the individual load-velocity relationship by applying a linear regression model as the load associated with an MV of 0.17 m/s. In addition, the MV obtained at each %1RM (i.e., from 20% 1RM to 80% 1RM in 20% increments), the load-velocity slope (i.e., the decrease in MV per each 1% of increment in the %1RM), and the y-intercept (i.e., the estimate of MV at 0% 1RM) were computed from the individual load-velocity relationships. No significant differences were observed between the 3 phases of the MC for any of the measured load-velocity relationship parameters (corrected p-value =0.495; effect size =0.24). The results suggest that the estimation of the BP 1RM from the load-velocity relationship seems not to vary over the 3 different phases of the MC (i.e., menstrual, follicular, and luteal phases).